2020
DOI: 10.1007/s00432-020-03219-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of circulating tumor DNA in hepatocellular and pancreatic carcinomas

Abstract: Hepatocellular carcinoma (HCC) and pancreatic cancer (PC) belong to the most lethal malignancies worldwide. Despite advances in surgical techniques and perioperative multidisciplinary management, the prognosis of both carcinoma entities remains poor mainly because of rapid tumor progression and early dissemination with diagnosis in advanced tumor stages with poor sensitivity to current therapy regimens. Both highly heterogeneous visceral carcinomas exhibit unique somatic alterations, but share common driver ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 159 publications
0
17
0
Order By: Relevance
“…Finally, our analysis supported the relationship between unresectable HCC with high intensity in the hepatobiliary phase of EOB-MRI and CTNNB-1 mutations determined by cfDNA analysis. The analysis of cfDNA is an effective method for the detection of genetic alterations in HCC [ 16 , 29 , 30 ], and it is less impacted by intratumoral heterogeneity than are analyses of single tumor tissue samples [ 31 ]. In three patients with unresectable HCC with high intensity in the hepatobiliary phase of EOB-MRI, CTNNB1 alterations in cfDNA were observed in two patients (66.7%, 2/3), while all four patients without HCC with iso-high intensity in the hepatobiliary phase of EOB-MRI lacked mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our analysis supported the relationship between unresectable HCC with high intensity in the hepatobiliary phase of EOB-MRI and CTNNB-1 mutations determined by cfDNA analysis. The analysis of cfDNA is an effective method for the detection of genetic alterations in HCC [ 16 , 29 , 30 ], and it is less impacted by intratumoral heterogeneity than are analyses of single tumor tissue samples [ 31 ]. In three patients with unresectable HCC with high intensity in the hepatobiliary phase of EOB-MRI, CTNNB1 alterations in cfDNA were observed in two patients (66.7%, 2/3), while all four patients without HCC with iso-high intensity in the hepatobiliary phase of EOB-MRI lacked mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common primary neoplasm of the liver. 120 Chen et al 121 found that METTL3 can promote the progression of liver cancer cells through YTHDF2-dependent transcriptional regulation of SOCS2 silencing. Further study showed that METTL14 interacted with DGCR8 and positively regulated the expression of miRNA 126.…”
Section: Review Llmentioning
confidence: 99%
“…ctDNA can reflect tumor cytogenetics and epigenetic information ( 7 ). In the whole-cycle management of HCC, ctDNA monitoring can dynamically provide the information of tumor genetic variation, which has become a hot research direction in recent years ( 8 ).…”
Section: Introductionmentioning
confidence: 99%